THE IMPACT OF AUDIT QUALITY, AUDIT COMMITTE, AND INTERNAL CONTROL SYSTEMS ON FINANCIAL REPORT QUALITY (IDX FINANCE SECTOR) - Sem, Dea Van; Hastuti, Theresia Dwi (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2024)
The objective of this study is to examine the impact of audit quality, audit committees, and internal control systems on the quality of financial reporting. The study population consists of financial companies listed on the IDX during the period 2018-2022. Secondary data in the form of annual reports were obtained from the website www.idx.co.id, and data were collected from 230 financial companies using the purposive sampling method. This study uses multiple linear regression analysis with the help of SPSS version 25. The results indicate that the internal control system has a positive impact on the quality of financial reports. However, neither audit quality nor audit committee has any effect on the quality of financial reports.